Risk Factors for Voice Disorders among Fado Singers: A Cross-Sectional Study - Pedro Pestana; Susana Vaz-Freitas; Maria Conceição Manso (MDPI AG, 2023)
Fado is an urban Portuguese musical style rooted in popular culture. Previously found data suggests that Fado singers may have an increased risk of developing voice disorders. (1) Aim: To determine the risk factors for the development of voice disorders among Fado singers. (2) Methods: A cross-sectional study was conducted through the administration of a questionnaire containing questions related to voice disorders in singers. The relationship between personal and social data, musical background, performance demands and habits, vocal health and wellbeing, and strategies to overcome voice problems are reported. Beyond a comprehensive characterization, odds ratios (ORs) and their 95% confidence intervals (CIs) for the association with voice disorders were calculated through univariate and multivariate logistic regression analyses. (3) Results: The significant risk factors for voice disorders were as follows in decreasing order: nose-related disorders; decongestants or antihistamines; oral contraceptives or hormone replacement therapy; previous smoking habits; and vocal fatigue after performances. (4) Conclusion: These activities significantly increased the risk of developing voice disorders. The evidence from this study and the relative low prevalence of self-reported voice disorders suggest that these singers may develop a kind of protective combination of factors beyond the scope of this research.